Implementation of Discovery Learning Model to Develop Students Ability in Comprehending Descriptive Text About Tourism Place at Junior High School - Sheren Raihany Dhivatunnisa; Muhammad Andriana Gaffar (FKIP - Universitas Riau, 2026)
Many junior high school students have difficulty comprehending descriptive text, especially in understanding the use of adjective vocabulary. Traditional teaching methods are often considered less effective in the learning activity. The purpose of this study is to investigate how the Discovery Learning model supports students in developing comprehension skills and encourages active participation during the learning process. This study employed a descriptive qualitative research design. Data were collected through classroom observation, interviews with the English teacher and students, questionnaires, and documentation of students’ learning activities. The data was managed by combining all collected data and additional sources, which were also analysed using triangulation. The findings show that the Discovery Learning model encourages students to be more active, curious, and engaged in their learning activities. Students were able to identify detailed information about the descriptive text about tourism places, especially regarding adjective vocabulary. In conclusion, the Discovery Learning model supports students’ comprehension and creates a more interactive learning environment.